2014
DOI: 10.3233/cbm-140416
|View full text |Cite
|
Sign up to set email alerts
|

The value of the pretreatment neutrophil lymphocyte ratio vs. platelet lymphocyte ratio in predicting the long-term survival in colorectal cancer

Abstract: Elevated pretreatment NLR is an independent predictor of both worse overall and disease free survival in colorectal cancer, whereas PLR was not after adjusting for confounding variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 30 publications
(62 reference statements)
1
42
2
Order By: Relevance
“…Several studies, including one of 140 patients with resectable CRLM, have found PLR to exert independent significance in CRC [35,45]. Other groups, however, have found the NLR, not the PLR, to exert an independent association with poor prognosis in patients with CRC [46,47]. Additional studies are needed, therefore, to further examine the prognostic value of the platelet count, and indices derived thereof, in the context of CRC and CRLM.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies, including one of 140 patients with resectable CRLM, have found PLR to exert independent significance in CRC [35,45]. Other groups, however, have found the NLR, not the PLR, to exert an independent association with poor prognosis in patients with CRC [46,47]. Additional studies are needed, therefore, to further examine the prognostic value of the platelet count, and indices derived thereof, in the context of CRC and CRLM.…”
Section: Discussionmentioning
confidence: 91%
“…Twenty-eight studies contributed data to the analyses of overall survival [2-7, 9, 11-31]. Significant heterogeneity was found among studies (I 2 = 81%, p = 0.000, Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The following studies confirmed this association [2, 3, 5, 6]. However, some other studies failed to demonstrate the association between pretreatment elevated platelet count and outcomes of colorectal cancer [1116]. Considering the controversial evidence, we conduct a meta-analysis to evaluate whether pretreatment elevated platelet count is a prognostic marker of colorectal cancer.…”
Section: Introductionmentioning
confidence: 82%
“…The majority of reports have shown NLR to be a novel biomarker of survival in primary and metastatic colorectal cancers [30,31,32,33,34,35,36]. A meta-analysis combining results from 49 studies containing 14,282 patients showed that higher values of NLR were associated with poor disease-free [hazard ratio (HR): 1.99; 95% CI = 1.80-2.20; p < 0.001] and overall survival (HR: 1.92; 95% CI = 1.64-2.24; p < 0.001) in solid cancer patients [2].…”
Section: Discussionmentioning
confidence: 99%